Pengaruh Green Trust, Green Price dan Green Brand Terhadap Minat Beli Produk Tas Merek Eiger di Kota Mataram - Azzahra Ariefta Quinola; Sulhaini Sulhaini (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to determine the influence of green trust, green price, and green brand on interest in purchasing Eiger brand bag products in Mataram City. Eiger is currently slowly producing environmentally friendly products, one of which is the Eiger brand environmentally friendly bag product. The type of research used is associative quantitative research. The analysis technique used was multiple linear regression using the SPSS version 25 program. This research was conducted in the Mataram City area by distributing questionnaires to 100 respondents from the age range of 17 years to more than 50 years. Using non-probability and purposive sampling techniques. The data used to analyze the relationship between variables is expressed on a numerical scale. The results of the analysis show: (1) The Green Trust variable has a positive effect on buying. (2) The green price variable has a positive effect. (3) The green brand variable has a positive effect on purchasing interest.